The Unfolded Protein Response in Lung Disease - Marcinak, Stefan J. (American Thoracic Society, 2010)
The early steps in the biogenesis of secreted and membrane proteins occur in the lumen of the endoplasmic reticulum (ER), where resident proteins that make up the ER machinery assist in their folding, maturation, and complex assembly. Variation in the load of ER client proteins and in the function of the organelle's aforementioned machinery for coping with that load can lead to an imbalance between the two that is referred to as ER stress. This triggers a cellular response, mediated by highly conserved signaling pathways that collectively restore equilibrium to the protein-folding environment in the organelle by increasing the expression of genes that enhance nearly all aspects of ER function, and by transiently repressing the biosynthesis of new client proteins. Evidence accrued over the past 10 years suggests that ER stress and response to it influence the fate of mutant proteins that fold inefficiently, impact on the functionality of cells and tissues that cope with unusual loads of ER client proteins, and intersect with signaling pathways that influence inflammation and cancer biology. Here, we review some of the basic workings of unfolded protein response and relate them to processes that are of potential relevance to pulmonary disease.